A personalized approach empowering successful aging: Patient perspective on fall prevention education. Issue 7 (27th July 2021) - Collins, Courtney E.; Schultz, Kurt; Mathew, Pawan; Chandra, Arnav; Nguyen, Bryan; Chen, Tiffany; Renshaw, Savannah; Rose, Karen M.; Santry, Heena P.
Abstract: Background: Falls are the leading cause of fatal injury, and the most common cause of nonfatal trauma, among older adults. However, patient perspectives on preferences for obtaining fall education are not well reported. Objective: To identify components of successful fall prevention education. Design: Prospective qualitative study. Setting: Tertiary care center; institutional. Participants: Adults aged 65 years or older with a history of falls who received services from inpatient trauma or outpatient geriatric services. Interventions: One‐hour face‐to‐face semistructured interview. Main Outcome Measure: Semistructured interviews sought to determine participants' history of fall education and perceived strengths and weaknesses of various formats of fall education. Results: Nearly all participants (9/10) indicated they had not received fall prevention education of any kind. Many participants (6/10) reported that, despite not receiving any formal education about falls, they had either given or received information about falls from other older adults in their communities. Participants indicated that framing fall education as a part of healthy aging would be more desirable and mentioned involving participants' families as part of the education. The majority of participants (7/10) suggested fall education be delivered through in‐person discussion with providers, and most (9/10) indicated this would provide a personalized approach with opportunity for questions. Participants specified fall education should consist of both environmental modifications (5/10) and awareness of one's surroundings (4/10). Conclusions: Despite histories of falls, nearly all participants reported they had not received formal fall education. However, many indicated they received fall information informally through their communities. Participants agreed successful fall prevention education would be delivered in an empowering way by a trusted member of the care team.